Struvite precipitation from biogas digestion slurry using a two-chamber electrolysis cell with a magnesium anode. (10th February 2018) - Lin, Xiaochang; Han, Zhiying; Yu, Hongjun; Ye, Zhangying; Zhu, Songming; Zhu, Jun
Abstract: A novel, two-chamber electrolysis cell equipped with an ion exchange membrane and a magnesium anode was proposed in this study to recover phosphate as struvite from both the simulated and real biogas digestion slurry of swine wastewater. In the electrolysis experiments with the simulated slurry, the optimal pH and current density were determined to be 8.5 and 22.2 A m −2, respectively, achieving 95% phosphate removal efficiency and 100% current efficiency. The phosphate removal rate was mainly dependent on the magnesium dissolving rate. In the electrolysis experiments with the real digestion slurry, the pH of slurry increased from 7.4 to around 8.7 after the cathode-anode sub-section electrolysis without adding chemical reagents, achieving 93% phosphate removal efficiency at 22.2 A m −2 . The phosphate removal efficiency could be kept constant in three consecutive electrolysis cycles with both the anion exchange membrane and the cation exchange membrane. The cost of the magnesium anode treatment for the real biogas digestion slurry for struvite recovery was estimated to be 81.57 kg −1 P, mainly resulting from the consumption of electricity and magnesium anode. The precipitates collected from all experiments were identified as struvite by the X-ray diffraction analysis. Highlights: Anolyte pH was kept at 8.4–8.7 using ion exchange membrane in electrolysis cell. Over 93% P was removed at current density of 22.2 A m −2 with no alkali supplement. Electrolysis costs of 81.57 kg −1 P are 17% lower than the costs of MgCl2 addition.